Lung Cancer Screening Uncertainty among Patients Undergoing LDCT - Hall, Daniel L. (Am J Health Behav, 2018)
OBJECTIVES: Lung cancer is the leading cause of cancer death, yet lung screening remains underutilized. Lung cancer screening uncertainty (LCSU), including referral clarity and the perceived accuracy of screening, may hinder utilization and represent an unmet psychosocial need. This study sought to identify correlates of LCSU among lung screening patients. METHODS: Current and former smokers (N = 169) completed questionnaires assessing LCSU, sociodemographic variables, objective and subjective numeracy, stress, and anxiety, as part of a cross-sectional study of lung screening patients at an academic hospital. RESULTS: Patients (52% current smokers) reported high clarity about the reason for their lung screening referral. Less clarity was associated with lower education, not receiving Medicare, and greater stress and anxiety. Patients perceived lung screening to be moderately accurate, and levels were inversely related to objective numeracy. Subjective numeracy was higher among former versus current smokers (OR = 2.5), yet was unrelated to LCSU variables. CONCLUSIONS: Several sociodemographic, numeracy, and emotional factors were associated with greater LCSU. With multiple policy and clinical guidelines purporting the uptake of annual lung screening, it is important to identify patients with LCSU and tailor shared decision-making to clarify their uncertainties.